Identifyng the relationships between personality traits and non-cognitive skills - Călin, Mariana Floricica; Radu, Andrei Mihai (Technium Social Sciences Journal, 2021)
Through this research, it has been studied the relationship between personality traits and non-cognitive skills. The hypotheses of this study are that there is a positive correlation between a high level of extraversion and physical abilities, and there is a positive correlation between a high level of autonomy and musical abilities. The research was conducted through two research tools, the purpose of which was to identify and evaluate personality traits and non-cognitive skills. The group of participants consists of 120 people aged between 18 and 33 years. The study results attest the validity of the assumptions. In both cases, personality traits are a possible predictor of the development of non-cognitive skills, while the latter are a possible modeling factor for the personality.